Impact of human disturbance on the biogeochemical silicon cycle in a coastal sea revealed by silicon isotopes. (11th September 2019) - Zhang, Zhouling; Sun, Xiaole; Dai, Minhan; Cao, Zhimian; Fontorbe, Guillaume; Conley, Daniel J.
Abstract: Biogeochemical silicon (Si) cycling in coastal systems is highly influenced by anthropogenic perturbations in recent decades. Here, we present a systematic study on the distribution of stable Si isotopes of dissolved silicate (δ 30 SiDSi ) in a highly eutrophic coastal system, the Baltic Sea. Besides the well‐known processes, diatom production and dissolution regulating δ 30 SiDSi values in the water column, we combined field data with a box model to examine the role of human disturbances on Si cycling in the Baltic Sea. Results reveal that (1) damming led to increased δ 30 SiDSi values in water but had little impacts on their vertical distribution; (2) decrease in saltwater inflow due to enhanced thermal stratification had negligible impacts on the δ 30 SiDSi distribution. An atypical vertical distribution of δ 30 SiDSi with higher values in deep water (1.57–1.95‰) relative to those in surface water (1.24–1.68‰) was observed in the central basin. Model results suggest the role of enhanced biogenic silica (BSi) deposition and subsequently regenerated dissolved silicate (DSi) flux from sediments. Specifically, eutrophication enhances diatom production, resulting in elevated exports of highly fractionated BSi to deep water and sediments. In situ sedimentary geochemical processes, such as authigenic clay formation, further fractionate Si isotopes and increase pore‐water δ 30 SiDSi values, which then leads to pore‐water DSi flux carrying higher δ 30 SiDSi compositions into deep water. Our findings provide new quantitative information on how the isotope‐based Si cycle responds to human perturbations in coastal seas and shed lights on shifts of Si export to open ocean.